IMPLEMENTATION OF EDUCATION MARKETING STRATEGIES IN IMPROVING SCHOOL COMPETITIVENESS IN SOUTH TANGERANG: A SYSTEMATIC LITERATURE REVIEW - Fitriyani, Syabrina; Supatmin, Supatmin (Yayasan Education and Social Center, 2025)
This study aims to analyze the implementation of education marketing strategies in improving school competitiveness in the South Tangerang region through an education management perspective using a systematic literature review with the PRISMA protocol which analyzes 20 reputable journal articles in the field of education management and education marketing for the 2019-2024 period. The study is focused on identifying effective marketing management models in the context of educational leadership and administration, with inclusion criteria including empirical studies of educational marketing management, leadership in school marketing, and educational institution marketing administration. The results of the analysis show that the implementation of education marketing management integrated with the school administration system can increase organizational effectiveness by up to 70%, with transformational leadership being a key factor in the successful implementation of strategies at the institutional level. A marketing management model centered on stakeholder satisfaction shows a significant improvement in the performance of educational organizations, while a structured marketing administration system allows schools to optimize resources and achieve organizational targets. Research limitations include a focus on English-language literature that can limit local perspectives in Indonesian education management and variations in the operational definition of education marketing management. The practical implications suggest that principals and education administrators need marketing management competencies to lead organizational transformation towards market orientation, with the school's organizational structure needing to be adapted to accommodate marketing functions as an integral part of education management. The originality of the research lies in the integration of educational management theory with marketing practices in the perspective of school administration and leadership that contributes to the development of the body of knowledge in contemporary educational management and administration.